Le choix des espaces communs dans l’habité, support écologique et solidaire - Nicole Roux; Camille Noûs (Développement Durable et Territoires)
The common spaces in housing, also called intermediary or common areas, are an in-between of the public and the private and contain a whole part of social life: from the garbage room to the bicycle garage, from the lift to the corridor, from the entrance hall to the car park, from the courtyard to the garden. So many places where behaviours can be analysed as markers of a relationship with the environment in its social and ecological dimensions. The article questions the design and uses of these spaces in different forms of habitat that are characterized by a involvement of the inhabitants in their management. The cases studies concern specific habitats, designed in successive periods: a cooperative of inhabitants in the 1950s, self-managed grouped habitats in the 1970s and 1980s, and a participatory housing in the 2000s. This socio-historical perspective makes it possible to observe the evolvement around solidarity and ecological choices by a population involved in the establishment of a different way of living, at the time of the changeover in the 21st century.